Evaluating frozen beef and meat packaging material exposed to low levels of ammonia gas - Hussain, Faris A. Karim (Kansas State University, 2009)
Ammonia leaks in meat chilling/frozen storage or processing facilities are not uncommon. Often the meat products are packaged in polymer films that theoretically protect the product from contamination. Unfortunately, there is almost no data on whether ammonia can permeate packaging films. The objectives of this study were to evaluated meat contaminated by low levels of ammonia under frozen storage conditions (-17 ± 3[degree]C), and further evaluated the permeability of common meat packaging films including: low density polyethylene (LDPE), 3 mil Cryovac (E-2300), and 3 mil vacuum (V-PA/PE) at freezing (-17 ± 3 [degree]C) and room temperatures (21 ± 3 [degree]C). Fresh beef Semitendinosus muscles were fabricated to form 10 x 5 x 2.3 cm steaks. The packaging films were fabricated into 10 x 5 cm pouches and filled with 50 mL deionized water. The meat and the pouches were exposed in a plexiglass enclosure, contained in a freezer, to 50, 100, 250, and 500 ppm ammonia gas (85 mL/min) for exposure times of 6, 12, 24, and 48 hr. The ammonia levels in the meat samples were 34.2 (50 ppm exposure), 51.5 (100 ppm exp.), 81.1 (250 ppm exp.), and 116 ppm (500 ppm exp.), and the pH values ranged from 5.56 to 5.75 (control ranged from 5.31 to 5.43) at 48 hr. At freezing temperatures, ammonia residues remained undetected, and no differences in pH were found in the pouches. At room temperature, all pouches were slightly permeable to ammonia; the levels observed in the pouches were, 7.77 ppm (pH, 8.64) for E-2300, 5.94 ppm (pH, 8.38) for LDPE, and 0.89 ppm (pH, 7.23) for V-PA/PE at 500 ppm exposure for 48 hr (unexposed samples pH ranged from 5.49 to 6.44). The results showed that meat packaging materials have low ammonia permeability and thus protect meat products exposed to ammonia exposure during frozen storage. Moreover, meat content is low even with ammonia exposures as high as 500 ppm for up to 48 hr.
Keywords: Ammonia; Meat contamination; Meat packaging; permeability; Agriculture, Food Science and Technology (0359)